Analysis of the Importance of Guidance and Counseling Services for Students - Sutirna Sutirna; Intisari Intisari (lppm Universitas Negeri Jakarta, 2022)
This study aims to describe the importance of guidance and counseling services for students, subjects in this study were students of mathematics education who are taking courses in guidance and counseling, This research method using a questionnaire in the form of a question and students respond via email, the results are analyzed, then tabulated in the frequency table of respondents, which is then presented with the number of perceptions. The results of this study found that the development of the era, family factors, IT development, excellent Guidance and Counseling services, individual development, individual experience, future and potential development are important guidance and counseling services for students to be well organized at every level of education. The conclusion from the results of this study is that guidance and counseling services must be carried out optimally at all levels of education, guidance and counseling services are important for students to be able to prepare and anticipate life and life, both for today and in the future, and guidance and counseling services. Counseling should be a place for students to consult various problems, not the other way around being a place that is feared by students.